JIB-04 improves PPARγ expression and enhances adipogenic differentiation efficiency in human umbilical cord mesenchymal stem cells - Xinping Qian; Tianyi Wen; Yi Zi; Ming Jin; Meihua Jin; Yanhua Jin (Biochemistry and Biophysics Reports, 2025)
Adipogenic differentiation of mesenchymal stem cells (MSCs) is a complex, multi-step cellular process involving proteins, genes, and metabolic levels. As an important epigenetic regulatory mechanism, histone modification has been extensively studied in adipogenic differentiation. However, its detailed mechanisms remain unclear, particularly regarding histone methylation, where existing research findings are inconsistent. JIB-04, a pan-histone lysine demethylase inhibitor, has recently gained significant attention in the medical field. In this study, JIB-04 was used as a pharmacological agent to investigate its role and underlying mechanism in the adipogenic differentiation of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs). The results revealed that JIB-04 promotes adipogenic differentiation by inhibiting the histone demethylase LSD1, thereby regulating the level of Histone H3 lysine 4 dimethylation (H3K4me2) at the promoter region of the key early adipogenic gene peroxisome proliferator-activated receptor gamma (PPARγ), leading to increased PPARγ expression. Furthermore, JIB-04 does not directly affect the expression of key genes or proteins involved in the middle and late stages of adipogenesis. Notably, a 24-h treatment with JIB-04 during the 21-day adipogenic differentiation process was sufficient to effectively enhance the overall adipogenic efficiency of the cells.